2022
DOI: 10.1097/upj.0000000000000321
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Preparation by Urology Trainees in 2021: The Interplay of Video and Print Resources

Abstract: Introduction:We investigate urology trainee preparation for surgical procedures by querying type and degree of video sources used and combination with traditional print materials for preparation of surgical procedures.Methods: An Institutional Review Board-approved 13-question REDCapÒ survey was distributed to 145 American College of Graduate Medical Education-accredited urology residency programs. Social media were also used to recruit participants. Results were collected anonymously and analyzed using ExcelÒ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
(40 reference statements)
0
2
0
1
Order By: Relevance
“…Mota et al conducted a survey and found that 98.6% of respondents had used videos, particularly from YouTube, to prepare for surgery [ 20 ]. A more recent study by Eccles et al found that, in a survey of 108 urology residents from 145 residency programs, YouTube was ranked as the primary reference for preparing for surgical procedures [ 21 ].…”
Section: Youtubementioning
confidence: 99%
See 1 more Smart Citation
“…Mota et al conducted a survey and found that 98.6% of respondents had used videos, particularly from YouTube, to prepare for surgery [ 20 ]. A more recent study by Eccles et al found that, in a survey of 108 urology residents from 145 residency programs, YouTube was ranked as the primary reference for preparing for surgical procedures [ 21 ].…”
Section: Youtubementioning
confidence: 99%
“…– 87% of 108 U.S. urology residents reported using videos for surgical preparation, 93% of which used YouTube [ 21 ]…”
Section: Other Apps and Platformsmentioning
confidence: 99%
“…Nach unserem Kenntnisstand findet sich im urologischen Bereich ein Defizit an qualitativ hochwertigen urologischen Operationsvideos für die ersten Abschnitte der Weiterbildung ("Anfängeroperationen"). Aktuelle Untersuchungen aus dem Jahr 2021 von Eccles [6] In der Summe wurden in allen Fragen hohe Werte vergeben (gut und sehr gut von 81,6-95,8 %, s. . Tab.…”
Section: Diskussionunclassified